THE ADOPTION OF LINGUISTIC PROCEDURES TO PRESERVE AND STRENGTHEN A SPACE OF FREEDOM, SAFETY AND JUSTICE IN THE EUROPEAN UNION - Tulekian, Isabelle (2022)
Linguistic rights and  the right to language, are essential for the exercise of many fundamental rights, namely freedom of expression, information and communication, as decisive instruments of democracy. In 2005, the European Charter for Plurilingualism highlighted plurilingualism as an essential vector of democratic citizenship. The Charter states that plurilingualism is the most desirable and effective form of communication in the space of public debate, developing values ​​of tolerance and acceptance of difference and minority groups. Inseparable from any form of active European citizenship, plurilingualism and cultural diversity are a fundamental component of European identity. It is recalled that the Charter of Fundamental Rights of the European Union enshrined the right to language in the European Union. Art. 21 affirms the principle of non-discrimination. Art. 22 privileges cultural, religious, and linguistic diversity. On the other hand, the right to interpretation and translation in the context of criminal proceedings was established to guarantee respect for fundamental rights of all citizens of the Member States within the scope of the area of ​​freedom, of security and justice in the EU. The transposition of the directive into the legislation of each Member State should correct situations of great linguistic precariousness existing in the judicial system of the Member States, representing a substantial advance in the preservation of the rights of populations that do not speak the official language of the country. This study intends to take stock of the situation in 2022, analyzing national legislation and practices in the EU and in Portugal.